One-Day Youth Red Cross Camp: Training High School Students in Splinting Techniques for School-Based Trauma Response - Rahmah, R. A. Gabby Novikadarti; Fauzan, Suhaimi; Neri, Ervina Lili; Saputra, Dikki; Pramana, Yoga; Maulana, M. Ali (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
Introduction: Emergencies resulting from accidents can occur in any setting, including schools. In Indonesia, the overall injury prevalence has been reported at 9.2%, with schools accounting for the second-highest setting for injuries (8.4%). Splinting is a core first-aid technique that helps stabilize suspected fractures and prevent further injury or complications. This community service program aimed to improve the knowledge and practical splinting skills of Youth Red Cross (PMR) members at SMA Negeri 1 Sungai Raya. Methods: A training-based intervention was delivered in a one-day camp format using lectures, demonstrations, and supervised hands-on practice. Training effectiveness was evaluated using pre- and post-tests to assess knowledge gains and structured observation during skills practice to assess performance. Results and Conclusion: Students’ knowledge increased substantially, as reflected by an improvement in mean test scores from 56.78 (pre-test) to 92.96 (posttest). Participants also demonstrated better adherence to correct splinting procedures during practice sessions. Overall, demonstration-centered training was effective for improving adolescents’ understanding and practical competency in splinting.